Theoretical aspects of corporate culture (Journal of Economic Research & Business Administration, 2017)
The aspects of corporate culture – the most important element of prosperityof the entities, shown in a value system, in the principles of structuraland personnel policy, traditions of the organization, the interpersonalrelations and in special internal environment of corporation are consideredin this article. Functions of corporate culture are determined, as well asa number of components of corporate culture which shall be acceptedand be supported by all members of the collective is shown. Positive andnegative corporate cultures are allocated, their role in increase of overallperformance or preventing to normal functioning of the organization andaccomplishment of its mission are shown. The main forms of existence ofcorporate values are considered: the ideals developed by a management;the embodiment of these ideals within the organization; internal motivationalstructures of the identity of staff of the organization. The increase ofthe level of corporate culture, forming of reasonable valuable orientations,isettings, regulations, the relations are the important conditions of effectivefunctioning of the organization.